A Method for Analysis of Nitrotyrosine-Containing Proteins by Immunoblotting Coupled with Mass Spectrometry - Kohutiar, Matej; Eckhardt, Adam (Methods in molecular biology (Clifton, N.J.), 2021)
Nitrotyrosine formation is caused by presence of reactive oxygen and nitrogen species. Nitration is a very selective process leading to specific modification of only a few tyrosines in protein molecule. 2D electrophoresis and western blotting techniques coupled with mass spectrometry are common methods used in analysis of proteome. Here we describe protocol for analysis of peroxynitrite-induced protein nitration in isolated mitochondria. Mitochondrial proteins are separated by 2D electrophoresis and transferred to nitrocellulose membrane. Membranes are then incubated with antibodies against nitrotyrosine. Positive spots are compared with corresponding Coomassie-stained gels, and protein nitration is confirmed with mass spectrometry techniques.
Keywords: Peroxynitrous Acid; Mass spectrometry; Animals; skot; hmotnostní spektrometrie; Mass Spectrometry; imunoblotting; srdeční mitochondrie; mitochondriální proteiny; Immunoblotting; Mitochondrial Proteins; 2D gelová elektroforéza; Nitrotyrosine; tyrosin; Electrophoresis, Gel, Two-Dimensional; zvířata; Cattle; 2D electrophoresis; kyselina peroxydusitá; Tyrosine; Mitochondria; Mitochondria, Heart